Multiple coverings of a closed set on a plane with non-Euclidean metrics by circles of two types - Bao, Phung The; Mung, Le Quang (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
The article is devoted to multiple covering problems for a closed set in a two-dimensional metric space by circles of two types. The number of circles of each class is given as well as a ratio of radii. This problem is as interesting and important as the classical circle covering problems. It is usually studied in the case when the distance between two points is Euclidean. We assume that the distance is determined using some particular metric arising in logistics, which, generally speaking, is not Euclidean. To solve this problem, we propose a computational algorithm based on a combination of the optical-geometric approach due to Fermat and Huygens principles and the Voronoi diagram. A key feature of the algorithm is the ability to deal with non-Euclidean metrics.